Enhancing Safety Culture in the Aviation Sector at East Kalimantan: A Study on Organizational, Group, and Individual Safety - Ida Ayu Indira Dwika Lestari; Dewi Novita Hardianti; Iwan M Ramdan; Muhammad Sultan; Ika Wulan Sari (Indonesian Journal of Global Health Research, 2025)
The aviation industry operates in a high-risk environment where safety is paramount. Despite the implementation of Safety Management Systems (SMS), aviation incidents often highlight gaps not in compliance, but in safety culture—how individuals and organizations perceive and prioritize safety. A mature and robust safety culture can significantly reduce accidents and improve operational reliability. This study aims to explore and describe the safety culture profile in the aviation sector, particularly focusing on the maturity of safety practices at the individual, group, and organizational levels. A cross-sectional study was conducted using the Nordic Occupational Safety Climate Questionnaire (NOSACQ-50), a validated instrument to assess safety culture. A total of 183 aviation workers from various operational units participated in the survey. In addition to quantitative analysis, focus group discussions (FGDs) were held with selected management and operational staff to provide contextual insights into survey findings. The results showed that the overall safety culture maturity level among respondents was categorized as proactive, with the highest scores in management commitment (85.0) and safety procedures (85.0). However, relatively lower scores were observed in risk perception (70.5) and work environment (70.0), indicating areas for targeted improvement. These findings suggest that while aviation organizations have made considerable progress in building a strong safety culture, further efforts are needed to enhance risk awareness at the individual level and improve environmental factors influencing safety behaviour. Interventions should emphasize participatory safety practices, continuous communication, and reinforcement of risk-based thinking